Pengaruh Pembelajaran Etika Bisnis Terhadap Kemampuan Pengambilan Keputusan Etis Mahasiswa Akuntansi - Ayu Dwi Janyanti; Fitri Dwi Anggraini; Tries Ellia Sandari (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to analyze the influence of business ethics learning on the ethical decision-making abilities of accounting students. The background of this research is based on the growing need for ethical competence among future accountants who are frequently confronted with moral dilemmas in professional practice. The study was conducted on 32 evening-class accounting students at the University of 17 August 1945 Surabaya who were enrolled in the Business and Professional Ethics course. A quantitative descriptive method was employed, and data were collected through questionnaires. The data were analyzed using normality testing, simple linear regression, and F and t tests to determine the significance of the variables. The normality test produced a significance value of 0.919, indicating that the data are normally distributed. The regression analysis revealed that business ethics learning has a significant effect on ethical decision making, supported by a significance value of 0.000. The R Square value of 0.516 indicates that 51.6% of the variance in ethical decision-making ability is explained by business ethics learning.